Bunker risk management strategies in liner shipping companies part I : operational measures to reduce bunker risk - Lee, Amanda Rui Fang. (2012)
As a result of bunker price volatility and overcapacity in the shipping market, shipping lines are facing increasing pressure to mitigate their exposure to bunker risk. Apart from fiscal measures, liner shipping companies can only exercise control over operational measures to reduce cost. Hence this is an area they should actively pursue to reduce cost. Using “K” Line as a case study, two cost models were developed to reduce operational cost through increasing efficiency and profitability and reduce operational costs where possible. The first model, called the slow steaming model, enables companies to minimize their cost expenditures by reducing the cruising speed of their fleet to a speed that is more cost effective. In essence the model depicts how speed can be traded for cost effectiveness. While the slow steaming model is effective in reducing bunker costs, operational challenges surrounding its implementation require liner shipping companies to develop other cost reducing operational capabilities to supplement slow steaming. This include the second cost model presented in this report, called the bunker port choice and quantity model, which shows how having a flexible bunker port choice and bunkering quantity result as part of the optimal bunkering strategy per voyage can reduce cost. Finally, the interdependency of these two cost models with the Bunker Adjustment Factor (BAF) and Financial Hedging is presented, revealing supplementary avenues for liner shipping companies to mitigate bunker risk through a comprehensive bunker risk mitigating strategy.